Season and host-community composition inside roosts may affect host-specificity of bat flies - Attila D. Sándor; Alexandra Corduneanu; Sándor Hornok; Andrei D. Mihalca; Áron Péter (Scientific Reports, 2024)
Abstract Bat flies are one of the most abundant ectoparasites of bats, showing remarkable morphological adaptations to the parasitic habit, while the relationship with their hosts is characterized by a high level of specificity. By collecting bat flies from live hosts, our intention was to elucidate the seasonal differences in bat fly occurrence and to describe factors regulating the level of incipient host specificity. Our results indicate that the prevalence and the intensity of infestation is increasing from spring to autumn for most host species, with significant differences among different fly species. Males showed higher infestation levels than females in autumn, suggesting a non-random host choice by flies, targeting the most active host sex. Bat-bat fly host specificity shows seasonal changes and host choice of bat flies are affected by the seasonal differences in hosts’ behavior and ecology, the intensity of infestation and the species composition of the local host community. Nycteribiid bat flies showed lower host specificity in the swarming (boreal autumn) period, with higher prevalence recorded on non-primary hosts. Choosing a non-primary bat host may be an adaptive choice for bat flies in the host’s mating period, thus increasing their dispersive ability in a high activity phase of their hosts.